Localization of production-destruction processes by distribution of phosphate in the estuaries of Uda and Usalgin Rivers (Okhotsk Sea) - A. S. Kurnosova; Y. I. Zuenko; M. G. Shvetsova (Известия ТИНРО, 2023)
The areas with prevalence of either production or decomposition of organic matter are localized in the estuaries of Uda and Usalgin Rivers (western coast of the Okhotsk Sea) on the data of chemical survey conducted in conditions of summer flood in July, 2016, interpreting patterns of non-conservative variations of inorganic phosphorus concentration (deflections of observed values from potential values determined by the river water mixing with the seawater). Sign of production-destruction balance changed along both surveyed estuaries: the organic matter decomposition prevailed in the internal estuaries but its production prevailed in the upper part of the external estuaries. Another common feature of both estuaries was active recycling: the larger portion of organics was produced with utilizing the phosphorus mineralized within the estuaries, but not the terrestrial phosphorus provided by the rivers ionic discharge. Extremely intensive recycling was observed in the Usalgin estuary that drained swampy lands.